(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2009)
Geographical conditions of the Tysa valley together with general characteristics of the natural vegetation (represented by forest, shrub, meadow, mire and aquatic vegetation) are given. Current state of meadow vegetation of the region is characterized in detail with mentioning four classes of formations: genuine, swampy, peaty and salt meadows. Anthropogenous transformation of meadow vegetation is considered as a result of presenthuman impact. Demutation schemes of the devastated ecosystems are described. Current tendency of the Tysa valley’s flora synanthropization is prevailing of apophytization of meadows and adventization of plaughed ecotopes.